2006
DOI: 10.1161/01.hyp.0000216717.72048.6c
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Retinal Microvascular Structure and Risk of Mortality From Ischemic Heart Disease and Stroke

Abstract: Abstract-Abnormalities of the retinal microcirculation are found in hypertension and diabetes and predict cardiovascular mortality. This study examined the relationship between abnormalities of the retinal microvasculature and death from ischemic heart disease (IHD) and stroke. A population-based, nested case-control study was undertaken within the Beaver Dam Eye Study. Subjects (43 to 74 years) who died of IHD (nϭ126) or stroke (nϭ28) over a 10-year period were age and gender matched with controls subjects (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
245
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(262 citation statements)
references
References 34 publications
13
245
1
3
Order By: Relevance
“…There have been studies suggesting that increased vessel tortuosity is related to diabetes-driven haemodynamic changes such as disturbed blood flow [11,22], tissue hypoxia [13], endothelial dysfunction [12,23], and increased levels of VEGF [15,16,24]. In persons with diabetes, hyperglycaemia-mediated hypoperfusion can initiate blood flow disturbance together with the loss of endothelium cells and pericytes of the vessel wall, leading to the loss of autoregulatory function of the vessels including its compensatory mechanisms for the fluctuating hydrostatic pressure [25].…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies suggesting that increased vessel tortuosity is related to diabetes-driven haemodynamic changes such as disturbed blood flow [11,22], tissue hypoxia [13], endothelial dysfunction [12,23], and increased levels of VEGF [15,16,24]. In persons with diabetes, hyperglycaemia-mediated hypoperfusion can initiate blood flow disturbance together with the loss of endothelium cells and pericytes of the vessel wall, leading to the loss of autoregulatory function of the vessels including its compensatory mechanisms for the fluctuating hydrostatic pressure [25].…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Several studies using novel retinal vascular features such as branching angles, bifurcation, fractal dimension, tortuosity, vascular length-to-diameter ratio and wall-to-lumen ratio have shown that these features may also be related to hypertension and may provide additional information in predicting cardiovascular diseases. 35,[37][38][39][40][41] More specifically, increased curvature as reflected by a greater retinal venular tortuosity and wider retinal venular caliber have been linked with elevated blood pressure. 35,42 Furthermore, smaller fractal dimension and smaller arteriolar branching asymmetry ratio have been shown to be associated with uncontrolled and untreated hypertension.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…Different analytical methods have hampered the comparison of results between studies, and application-common methods in different studies will allow data pooling to generate more valid risk estimates. Additionally, the role of novel measures of retinal vascular structure (99,103,(111)(112)(113) in predicting diseases remains to be determined.…”
Section: Implications For Research and Clinicalmentioning
confidence: 99%